Estimation of the lactate threshold by near infrared spectroscopy - Welford D. J.; Sellens, M.; Thomson, S.; Cooper, C. E. (Oxygen transport to tissue XXI, 1999)
It has been shown that near infrared spectroscopy (NIRS) is a valid method for monitoring blood volume and oxygenation changes in human muscle [1]. Previous studies have shown a significant relationship between tissue deoxygenation measured by NIRS and gas exchange measurements used to determine the ventilatory threshold [2]. A significant relationship has also been seen between blood lactate concentration and tissue deoxygenation [3]. In this study a continuous wave dual wavelength near infrared system (MRM 96) was used to monitor blood volume and oxygenation changes during an incremental cycle exercise test to exhaustion. Method: The incremental cycle ergometer protocol was the same as described by Bhambhani [1]. Near infra-red spectroscopy measurements were taken from the right vastus lateralis simultaneously with gas exchange measurements taken using open circuit spirometry ( Oxycon beta). Blood samples for lactate measurements were taken at the end of every two minute increment. Results: An initial deoxygenation of the muscle was seen approximately three minutes into the exercise (Fig 1.). This was accompanied by a significant increase in blood volume. Throughout the exercise period the muscle blood volume rise correlated to the increase in global oxygen consumption, mirroring the known correlation between rises in muscle blood flow and muscle oxygen consumption. Interestingly the point at which lactate rose above the baseline (lactate threshold) correlated best with a change in the rate of the blood volume increase, rather than a change in the muscle oxygenation.